Feline cutaneous lymphoma: an evaluation of disease presentation and factors affecting response to treatment. Issue 4 (April 2022) - Siewert, Jacob; Pellin, MacKenzie A; Husbands, Brian D; Curran, Kaitlin M; Scavelli, Diane; Sampene, Emmanuel
Objectives: The primary goal of this study was to characterize the clinical presentation of feline cutaneous lymphoma. The secondary aims included determining if treatment or initial response to treatment affected the overall survival of patients, and understanding if disease characteristics such as immunophenotype, cell size or the presence of epitheliotropism influenced response to treatment. Methods: Veterinary medical oncologists at four academic veterinary teaching hospitals submitted cases of feline patients with cutaneous lymphoma diagnosed by histopathology or cytology. Signalment, feline leukemia virus (FeLV)/feline immunodeficiency virus (FIV) status, physical examination findings, clinical signs, diagnostic tests, therapy, response and outcome, and necropsy findings, when available, were recorded. Results: Forty-one patients were identified and described. The majority of patients were domestic shorthair cats (n = 29). The median age at diagnosis was 12.3 years. Males were over-represented in the population (n = 30). In the majority of patients (n = 33), the FIV/FeLV status was unknown. Twenty patients were fully staged. Thirty-four patients were treated with a variety of modalities, including surgery, radiation, single-agent or combination chemotherapy, or prednisolone only. In multiple patients, surgery or radiation was combined with a systemic therapy. Of 34 patients treated with some form of therapy, 20 responded (achieving either a partial response or complete remission). Conclusions and relevance: Clinical signs and physical examination findings varied among patients. Response to therapy appeared to be associated with survival (P = 0.0025); however, this population was highly censored. Immunophenotype, cell size and the presence of epitheliotropism did not influence treatment response. Results were limited by small numbers of patients, heterogeneous disease manifestations and treatment protocols. Further studies are necessary to evaluate the effect of specific treatment modalities and disease subtype on prognosis.